2012
DOI: 10.1371/journal.pone.0051148
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Crosstalk between Stress-Induced Gastric Ulcer and Depression under Chronic Stress

Abstract: Stress contributes to a variety of diseases and disorders such as depression and peptic ulcer. The present study aimed to investigate the correlation between stress ulcer and depression in pathogenesis and treatment by using chronic stress depression (CSD), chronic psychological stress ulcer (CPSU) and water immersion restrain stress models in rats. Our data showed that the ulcer index of the animals after CSD exposure was significantly higher than that of controls. Depression-like behaviors were observed in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 47 publications
1
30
0
4
Order By: Relevance
“…Stressors activate the par ventricular nucleus, giving rise to the release of corticotropin-releasing hormone (CRH), and CRH acts on the pituitary and stimulate the secretion of ACTH, which promotes glucocorticoids release from the adrenal cortex (Herman and Cullinan 1997). Glucocorticoids can not only interfere with tissue Table 3 Effect of methanolic extract of Fumaria indica (MFI), monomethyl fumarate (MMF), and Withania somnifera root extract (WS) on weight of glandular portion of stomach and mucosal parameters in chronic foot-shock stress rats repair, elevate levels of gastric acids and pepsin, but also reduce the secretion of gastric mucus, and eventually impair gastric mucosal barrier resulting in peptic ulcer (Zhang et al 2012). Foot shocked animals are known to activate stress-responsive systems in both brain and peripheral organs, including increased HPA-axis activity Swanson 1981, 1982;Rivest and Rivier 1991) as well as increase in pro-inflammatory cytokine levels both in blood (Morrow et al 1993) and brain (Deak et al 2003(Deak et al , 2005Blandino et al 2006Blandino et al , 2009Arakawa et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Stressors activate the par ventricular nucleus, giving rise to the release of corticotropin-releasing hormone (CRH), and CRH acts on the pituitary and stimulate the secretion of ACTH, which promotes glucocorticoids release from the adrenal cortex (Herman and Cullinan 1997). Glucocorticoids can not only interfere with tissue Table 3 Effect of methanolic extract of Fumaria indica (MFI), monomethyl fumarate (MMF), and Withania somnifera root extract (WS) on weight of glandular portion of stomach and mucosal parameters in chronic foot-shock stress rats repair, elevate levels of gastric acids and pepsin, but also reduce the secretion of gastric mucus, and eventually impair gastric mucosal barrier resulting in peptic ulcer (Zhang et al 2012). Foot shocked animals are known to activate stress-responsive systems in both brain and peripheral organs, including increased HPA-axis activity Swanson 1981, 1982;Rivest and Rivier 1991) as well as increase in pro-inflammatory cytokine levels both in blood (Morrow et al 1993) and brain (Deak et al 2003(Deak et al , 2005Blandino et al 2006Blandino et al , 2009Arakawa et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of glucocorticoids may induce or aggravate peptic ulcers, as systemic glucocorticoid treatment is clinically associated with an increased risk of peptic ulcer bleeding (Olsen et al, 2010), and administration of glucocorticoids to experimental animals can result in acute gastric erosion (Filaretova, 2011). Gastric bleeding in rats exposed to acute water immersion and restraint has been attributed to decreased gastric pH and elevated ACTH levels (Zhang et al, 2012). Previous research reported that zinc-deficient rats had higher CORT concentrations after exposure to water-immersion and forced swimming stress, suggesting that zinc supplementation might attenuate cold restraint-induced psychological stress (Watanabe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Stress ulcers are one of the most common stress-related disorders that affect the digestive system (Zhang et al, 2012). Severe physical stress is closely associated with gastric ulceration, even in Helicobacter pylori-negative patients (Moriya et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Further, chronic stress recapitulates many behavioral characteristics of depression that respond to antidepressants (Willner 2005). Hence, the pathophysiology of depression is intimately intertwined with stress (Zhang et al 2012), while the latter also has an effect on the mechanisms of neuroplasticity (Shors et al 1989;McEwen 1999McEwen , 2002.…”
Section: Stress-related Depressionmentioning
confidence: 98%